Small Movements, Big Impact - L. Dobashi Nunes; E. Dobashi Nunes; E. Rodrigues de Lima; R.F. Nunes (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
This article describes a practical example of a social & community engagement work and involvement of students with a focus on learning process activities. In 2008, the Gonçalinho project in Cáceres, Brazil, started a cooperation with the Brazilian AG at “Metzinger Gymnasium” in Germany. The result of a cooperation agreement signed between UNEMAT and the Educating and Cultural Society of BrazilianGerman Integration in 2012 provided the opportunity to promote the exchange of solidarity and human experiences between young people from both countries. This project has a particular historical background regarding the involvement of children with drugs and dealers. In this regard, the project aims to find a way to move children from those risks and involvement with criminality to get a clear perspective on life with more dignity. Therefore, this paper shows the strategies and challenges behind this community service and the students’ contribution based on a five-pillar methodology. Further opportunities regarding the next steps will be highlighted, along with practical lessons learned.